Iodine Requirements in Pediatrics: From Fetal Life to Adolescence - Iannuzzo, Gabriella; Campanozzi, Angelo; Trevisani, Viola; Rutigliano, Irene; Abate, Veronica; Rendina, Domenico; De Filippo, Gianpaolo (Frontiers in Endocrinology, 2022)
The aim of this mini-review is to present the current knowledge on iodine requirements in developmental age, from conception to adolescence. It is based on the analysis of updated national and international guidelines on iodine intake and the prevention of iodine deficiency. Health policy initiatives carried out in industrialized countries in previous decades have led to a dramatic improvement in nutritional iodine status in the general population. However, the prevention of iodine deficit continues to be a concern, especially for vulnerable categories, like adolescents and pregnant women.